Efeitos agudos da terapia de fotobiomodulação combinada com o campo magnético estático sobre a mobilidade funcional de pacientes pós-AVC: um ensaio clínico randomizado, placebo controlado, cruzado e triplo-cego - Dumont, Arislander Jonathan Lopes (2020)
Stroke is caused by an interruption in the blood supply to the brain and occurs when an artery that supplies blood supply to the central nervous system is blocked or ruptures. After the stroke, patients may show various levels of motor impairment and disability. The effects of PBMT are photochemical and photophysical, meaning that light is absorbed and causes a chemical change in tissues. The use of static magnetic field (sMF) demonstrated remarkable synergy, leading to enhanced electron transfer and consequent activation of mitochondrial respiratory chain and ATP production. However, in order for PBMT/sMF to be used more often and actually become an adjunctive tool in the rehabilitation of stroke survivors, some important aspects need to be clarified, particularly with regard to the dose and other parameters to be used in this population. Therefore, we aimed to identify the ideal dose of PBMT with different light sources (laser and LED) combined with sMF and determine its on functional mobility, static balance, and on space parameters -temporal and kinematic gait of post-stroke patients. Was conducted a randomized, placebo-controlled, crossover, triple-blind, clinical trial (RCT). Twelve patients were recruited, however ten concluded the study, they were randomly treated with four PBMT/sMF doses (placebo, 10 J, 30 J, and 50 J per site irradiated), with 1week interval washout between treatments. PBMT/sMF was administered after the pre-intervention (baseline) evaluation and the total energy delivered per site at each treatment was determined based on the results of the randomization procedure. PBMT/sMF were administered in direct contact with the skin and applied with slight pressure to nine sites on the knee extensors, six sites on the knee flexors, and two sites on the plantar flexors’ muscles in both lower limbs (bilaterally). PBMT/sMF was administered using a cluster of 12 diodes: four laser diodes of 905 nm (mean power of 0.3125 mW and peak power of 12.5 W for each diode), four LED diodes of 875 nm (mean power of 17.5 mW for each diode), four LED diodes of 640 nm(mean power of 15mWfor each diode), and a magnetic field of 35 mT. The following evaluations were carried out: 6-minute walk test (6MWT), timed and up go test (TUG), three-dimensional gait analysis and center of pressure (CoP) oscillation. Statistical analyzes showed significant improvement in the 6MWT and TUG (p <0.05) at dose 30J compared to placebo, at the 6MWT at dose 30 J (p <0.01) compared to baseline, at TUG dose 30 J (p<0.05) in relation to baseline. The statistical analysis did not show significant differences (p>0.05) in the CoP variables. In the spatiotemporal parameters of the gait, no statistically significant differences were found. However, statistically significant differences (p<0.05) were observed in the kinematic variables of the hip, specifically in the maximum and minimum flexion/extension angulation during the support phase. The use of TFBM with different light sources and wavelengths combined with CME had positive effects on functional mobility and on the kinematic gait variables of post-stroke patients. However, no statistically significant results were found in static balance and spatio-temporal parameters of gait in this population.